Ethnomedicinal Knowledge of Coastal Lampung Ethnic Group: A Study of Medicinal Plants Used in Pesisir Selatan, Indonesia - Ulmillah, Aulia; Dwijowati Asih Saputri; Putra, Kurnia Mansa (BiosciED: Journal of Biological Science and Education, 2025)
Indonesia is renowned for its high biodiversity and rich cultural heritage, particularly in traditional medicine practices among indigenous communities. The Coastal Lampung ethnic group in Pesisir Selatan, West Pesisir Regency, preserves a wealth of ethnomedicinal knowledge that has been underdocumented. This study aims to analyze the diversity, usage, and cultural significance of medicinal plants used by this community to support conservation efforts and provide a foundation for pharmacological research. Employing qualitative and quantitative ethnobotanical methods, including semi-structured interviews and field observations with 35 purposively selected informants, data were analyzed using the Index of Cultural Significance (ICS) and Species Use Value (SUV). A total of 79 medicinal plant species from 44 families were identified, used to treat ailments such as wounds, fever, cough, stomach disorders, and postpartum care, with leaves being the most commonly utilized plant part. Curcuma longa L., Zingiber officinale Rosc., and Citrus limon (L.) Osbeck had the highest cultural significance and use values, highlighting their importance in local healthcare. These findings underscore the critical need to conserve both ethnomedicinal knowledge and biodiversity, as well as to pursue pharmacological validation of key species, supporting the integration of traditional knowledge into sustainable health and biodiversity management strategies in Indonesia